Orthogonal projection and minimal linear interpolation on a n-dimensional cube - M. V. Nevskij (Моделирование и анализ информационных систем, 2007)
Let H be the orthogonal projection onto polynomials of n variables of degree < 1 and \\ \\ be the norm of an operator from C ([0,1]n) to C ([0,1]n). In this paper we show that C1On